Pricing longevity derivatives via Fourier transforms - Bravo, Jorge M. (2021)
Bravo, J. M., & Nunes, J. P. V. (2021). Pricing longevity derivatives via Fourier transforms. Insurance: Mathematics and Economics, 96(January), 81-97. [Advanced online publication on 1 November, 2020]. Doi: https://doi.org/10.1016/j.insmatheco.2020.10.008 ---%ABS3%